Instructional Management of Extracurricular Organizations in Private Higher Education Institutions - Zhang, Xuesong (Journal of Research in Vocational Education, 2026)
In the context of rapid socioeconomic development, people's attention to higher education is constantly increasing. As an important component of higher education, private universities are receiving widespread attention from all sectors of society. Shaanxi Province is a major province in education, with a large number of private universities. To comprehensively strengthen the teaching management of private universities, it is necessary to pay attention to the continuous optimization of management models, guided by promoting the comprehensive development of students' morality, intelligence, physical fitness, aesthetics, and labor. Foreign countries pay attention to the educational value of physical education teaching. The club teaching management model is a major breakthrough in traditional physical education teaching. In physical education teaching at private universities, club teaching management provides basic guidance, which can greatly improve the overall effectiveness of physical education teaching and provide protection for the development of students' comprehensive quality. This article analyses the problems faced by the teaching management of clubs in private universities in Shaanxi Province and proposes practical strategies to comprehensively strengthen the teaching management of clubs for reference.